The Bright Side of Artificial Intelligence in Corporate Leadership: A Rapid Literature Review of the Past Five Years - Nyoto, Nyoto; Nyoto, Rebecca La Volla; Renaldo, Nicholas (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
Artificial intelligence (AI) has emerged as a transformative force in corporate leadership, significantly reshaping how organizations operate and adapt in an increasingly digital world. As AI continues to evolve, understanding its impact on leadership practices is crucial for organizations seeking to stay competitive. This study employs a Rapid Literature Review approach to explore AI's beneficial impacts on corporate leadership over the last five years, synthesizing findings from 21 research articles. The PRISMA 2020 framework is used to select the articles for review, and Atlas.ti is applied to identify patterns in the literature and label the findings. The analysis reveals five key domains where AI demonstrates significant benefits, including building trust and ethical governance, enhancing decision-making and strategic insights, improving collaboration and team dynamics, increasing operational efficiency and productivity, and fostering emerging leadership dimensions. The findings highlight how AI embeds transparency and accountability, supports data-driven decision-making, and optimizes human resource processes. Additionally, AI fosters innovation by enabling leaders to adopt inclusive practices. This study provides valuable insights for leaders seeking to leverage AI for sustainable growth, emphasizing its potential in reshaping corporate leadership. By understanding and implementing these benefits, organizations can position themselves to thrive in the era of digital transformation.